Karakteristik Ekstrak Daun Bidara (Ziziphus mauritiana L.) Pada Perlakuan Ukuran Partikel Dan Lama Ekstraksi Menggunakan Metode Microwave-Assisted Extraction - Apsari, Ni Putu Somya Anindita; Wartini, Ni Made; Antara, Nyoman Semadi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
The bidara plant (Ziziphus mauritiana L.) is one of the plants commonly found growing wild in dry land areas. The leaves of bidara are rich in bioactive compounds such as saponins, alkaloids, glycosides, flavonoids, terpenoids, phenolic compounds, and have antioxidant activity. This study aims to investigate the effect of particle size and extraction time on the characteristics of the bidara leaf extract using the Microwave-Assisted Extraction method and to find the best combination treatment of particle size and extraction time to produce bidara leaf extract. This research is an experimental study designed using a Randomized Block Design (RBD) with a factorial experimental pattern. Two factors were tested: particle size consisting of 40, 60, and 80 mesh, and extraction time consisting of 11, 13, and 15 minutes. The data were analyzed using Analysis of Variance (ANOVA) and further tested using Duncan’s Multiple Range Test (DMRT). The research results show that both treatment of particle size and extraction time has a significant effect on yield, saponin content, foam height, and antioxidant capacity. Interaction of both treatments has a significant on the yield, while saponin content, foam height, and antioxidant capacity no significant effect. The best treatment with the effective index test is the treatment with a particle size of 60 mesh and an extraction time of 15 minutes, with characteristics of yield 29.38±0.57 percent, saponin content 18.15±0.64 percent, foam height 8.89±0.19 mm, antioxidant capacity 4.06±0.81 mg GAEC/g. Keywords: antioxidant, bidara leaves, extraction time, particle size, saponin.